Encephalitis with Autoantibodies against the Glutamate Kainate Receptors GluK2. Issue 1 (17th May 2021) - Landa, Jon; Guasp, Mar; Míguez‐Cabello, Federico; Guimarães, Joana; Mishima, Takayasu; Oda, Fumiko; Zipp, Frauke; Krajinovic, Vladimir; Fuhr, Peter; Honnorat, Jerome; Titulaer, Maarten; Simabukuro, Mateus; et al.
Abstract : Objective: The objective of this study was to report the identification of antibodies against the glutamate kainate receptor subunit 2 (GluK2‐abs) in patients with autoimmune encephalitis, and describe the clinical‐immunological features and antibody effects. Methods: Two sera from 8 patients with similar rat brain immunostaining were used to precipitate the antigen from neuronal cultures. A cell‐based assay (CBA) with GluK2‐expressing HEK293 cells was used to assess 596 patients with different neurological disorders, and 23 healthy controls. GluK2‐ab effects were determined by confocal microscopy in cultured neurons and electrophysiology in GluK2‐expressing HEK293 cells. Results: Patients' antibodies precipitated GluK2. GluK2 antibody‐specificity was confirmed by CBA, immunoprecipitation, GluK2‐immunoabsorption, and GluK2 knockout brain immunohistochemistry. In 2 of 8 samples, antibodies reacted with additional GluK2 epitopes present in GluK1 or GluK3; in both, the reactivity was abrogated after GluK2 immuno‐absorption. Six of 8 patients developed acute encephalitis and clinical or magnetic resonance imaging (MRI) features of predominant cerebellar involvement (4 presenting as cerebellitis, which in 2 patients caused obstructive hydrocephalus), and 2 patients had other syndromes (1 with cerebellar symptoms). One of the samples showed mild reactivity with non‐kainate receptors (alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors [AMPAR] and N‐methyl‐D‐aspartate receptors [NMDAR]) leading to identify 6 additional cases with GluK2‐abs among patients with anti‐AMPAR (5/71) or anti‐NMDAR encephalitis (1/73). GluK2‐abs internalized GluK2 in HEK293 cells and neurons; these antibody‐effects were reversible in neurons. A significant reduction of GluK2‐mediated currents was observed in cells treated with patients' GluK2 serum following the time frame of antibody‐mediated GluK2 internalization. Interpretation: GluK2‐abs associate with an encephalitis with prominent clinicoradiological cerebellar involvement. The antibody effects are predominantly mediated by internalization of GluK2. ANN NEUROL 2021;90:107–123